2009
DOI: 10.1038/hr.2009.58
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine gene polymorphisms in preeclampsia and eclampsia

Abstract: The clinical spectrum of preeclampsia (PE) ranges from mild hypertension to severe vasospasm associated with convulsions and multiple organ damage. The biological factors that determine the progression of PE to eclampsia (E) are unknown. Endothelial cell activation seems related to an impaired maternal immune response. The production of cytokines, IL-10 and TGF-b1, is apparently suppressed, and altered IL-2/IL-10 and TNF-a/IL-10 ratios have been reported in preeclamptic cases. The relationship between PE and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 47 publications
(56 reference statements)
2
38
1
Order By: Relevance
“…2 The development of pre-eclampsia is influenced by both genetic and environmental risk factors, suggesting its multifactorial inheritance. [3][4][5][6][7][8][9][10][11][12] Soluble fms-like tyrosine kinase-1 (sFlt-1), the naturally occurring soluble form of vascular endothelial growth factor receptor 1 (VEGFR1), is produced by alternative splicing of the Flt-1 transcript, resulting in a deletion of the intracellular and transmembrane domains of Flt-1. sFlt-1 binds VEGF and placental growth factor (PlGF) with high affinity, acting as a soluble trap of these angiogenic factors.…”
Section: Introductionmentioning
confidence: 99%
“…2 The development of pre-eclampsia is influenced by both genetic and environmental risk factors, suggesting its multifactorial inheritance. [3][4][5][6][7][8][9][10][11][12] Soluble fms-like tyrosine kinase-1 (sFlt-1), the naturally occurring soluble form of vascular endothelial growth factor receptor 1 (VEGFR1), is produced by alternative splicing of the Flt-1 transcript, resulting in a deletion of the intracellular and transmembrane domains of Flt-1. sFlt-1 binds VEGF and placental growth factor (PlGF) with high affinity, acting as a soluble trap of these angiogenic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Both genetic and environmental factors contribute to the pathogenesis of PE, and gene-environmental interactions may modulate PE risk. [1][2][3][4][5][6][7] Large epidemiological studies have shown that women with a history of early-onset severe PE, which means clinical manifestations occurring before 32 weeks of gestation, show an increased risk of cardiovascular diseases. 8 The renin-angiotensin system has been shown to be important in the pathogenesis of PE.…”
Section: Introductionmentioning
confidence: 99%
“…CRP is a non-specific biomarker of inflammation, which is closely associated with tissue injury (29). IFN-γ is also a potent pro-inflammatory cytokine resulting in damage of tissue (30). Comprehensive analysis of the anti-inflammatory effects of certain drugs revealed that they reduced the permeability of blood vessels, inhibited inflammatory corpuscle inflow to the inflammatory site and reduced the release of inflammatory factors, which indicated that these effects may be a cascading reaction.…”
Section: Fsc-mentioning
confidence: 99%